Analysis of Aeromagnetic Data for Enhancing Geologic Features Using Filtering Techniques Over the Congo Craton–Pan-African Belt Contact, Centre-East Cameroon - Jean Aimé Mono; Apollinaire Bouba; Olivier Ulrich Igor Owono Amougou; Jean Daniel Ngoh; Françoise Martine Enyegue A. Nyam; Théophile Ndougsa Mbarga (International Journal of Geophysics)
The Pan-African mobile zone, situated at the margin of the Congo Craton in Cameroon, is characterized by a geological setting with polyphased tectonics, which can be summarised as the alternation of compression and extension events. The present study, conducted in a portion of the aforementioned zone, is aimed at investigating crustal structures using aeromagnetic data. To achieve this, a variety of advanced analysis and interpretation techniques were applied to reduce aeromagnetic data at the equator, including total horizontal derivative (THD), Centre for Exploration Targeting (CET), 3D Euler deconvolution (ED), spectral analysis, and 2D3/4 modeling. The results indicate that the study area can be divided into four magnetic units based on the magnetic properties (magnetic susceptibility, geometry, and depth) of the underlying rocks. The THD method reveals the presence of pseudocircular and linear structures, which are associated with mafic intrusions and faults, respectively. The structural trends of the lineament generated semiautomatically using the CET method suggest that the structures are oriented in order of priority: E-W, WNW-ESE, ENE-WSW, and NE-SW. These directions are probably related to the Pan-African orogeny. According to the ED, the depths of these lineaments extend beyond 1250 m. A spectral analysis conducted on a profile intersecting some of the significant anomalies on the reduction to the equator (RTE) map indicates that the average depths of superficial and deep magnetic sources along this profile are approximately 0.5 and 6.5 km, respectively. The geological model obtained along this profile by direct 2D3/4 modeling indicates the presence of an ancient granitic basement, which is overlain by younger formations belonging to the Pan-African.